2021
DOI: 10.1039/d1sc00811k
|View full text |Cite
|
Sign up to set email alerts
|

FLP-type nitrile activation and cyclic ether ring-opening by halo-borane nonagermanide-cluster Lewis acid–base pairs

Abstract: Even though homoatomic nine-atom germanium clusters are known for two decades, their chemical properties are still rarely investigated. We now discovered that Zintl ion main group-element clusters posess a highly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 64 publications
1
24
0
6
Order By: Relevance
“…To test the potential of unsolvated 2 to act as an FLP, we therefore envisaged using a solvent that ensures the formation of 2 through breakup of the diorganoaluminum dimers and that at the same time can be considered as substrate for FLP reactivity. We regarded THF suitable for this approach, since the ring-opening of THF has been reported in literature in the context of main group-based FLPs, even before their recognition as such. When lithiated 1 was reacted with in situ generated Mes 2 AlCl­(thf) at −78 °C in toluene and subsequently warmed to room temperature, 31 P NMR spectroscopy revealed the formation of a prominent species at δ­( 31 P) = −22.5 ppm. This resonance was attributed to the coordinated FLP 2-THF , as the chemical shift closely resembles the one of 2-Et 2 O .…”
Section: Resultsmentioning
confidence: 99%
“…To test the potential of unsolvated 2 to act as an FLP, we therefore envisaged using a solvent that ensures the formation of 2 through breakup of the diorganoaluminum dimers and that at the same time can be considered as substrate for FLP reactivity. We regarded THF suitable for this approach, since the ring-opening of THF has been reported in literature in the context of main group-based FLPs, even before their recognition as such. When lithiated 1 was reacted with in situ generated Mes 2 AlCl­(thf) at −78 °C in toluene and subsequently warmed to room temperature, 31 P NMR spectroscopy revealed the formation of a prominent species at δ­( 31 P) = −22.5 ppm. This resonance was attributed to the coordinated FLP 2-THF , as the chemical shift closely resembles the one of 2-Et 2 O .…”
Section: Resultsmentioning
confidence: 99%
“…to form the keteniminate moieties (CvCvN), 9,[16][17][18] and so on. [19][20][21] These reactions can be mediated by a variety of metal complexes (mostly mononuclear ones). [4][5][6][7][8][9][10][11][14][15][16][17][18][19][20][21] In recent years, the low-valent metal-metal-bonded compounds have been increasingly employed in small molecule activation.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] These reactions can be mediated by a variety of metal complexes (mostly mononuclear ones). [4][5][6][7][8][9][10][11][14][15][16][17][18][19][20][21] In recent years, the low-valent metal-metal-bonded compounds have been increasingly employed in small molecule activation. [22][23][24][25] Especially, for the Mg-Mg bond, several reaction types are known toward nitriles (and isonitriles).…”
Section: Introductionmentioning
confidence: 99%
“…16 In 2019, Fässler showed that even early transition metal complexes of [Ge 9 (Hyp) 3 ] − and [Ge 9 (Hyp) 2 ] 2− are accessible, 17 and boron substituents could also be introduced. 18 The recent syntheses of alkyl phosphine gold germanium clusters like (Bu 3 P)Au-Ge 9 (Hyp) 3 offered a deeper insight into the ligand strength of the germanium cluster [Ge 9 (Hyp) 3 ] − , showing that its ligand strength in transition metal chemistry is between aryl and alkyl phosphines. 19 Further reactions of functionalized intermetalloid clusters MGe 9 (Hyp) 3 give access to intermetalloid clusters where Ge 9 R x units are bound to different transition metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…16 In 2019, Fässler showed that even early transition metal complexes of [Ge 9 (Hyp) 3 ] − and [Ge 9 (Hyp) 2 ] 2− are accessible, 17 and boron substituents could also be introduced. 18…”
Section: Introductionmentioning
confidence: 99%